An Evaluative Review of Recycled Waste Material Utilization in High-Performance Concrete - Al Mashhadani D. A. Jasim; Leong Sing Wong; Sih Ying Kong; Ahmed W. Al-Zand; Midhin A. K. Midhin (Salehan Institute of Higher Education, 2023)
The disposal of waste materials and their adverse effects on the environment have become a worldwide concern, disturbing the fragile ecological equilibrium. With growing awareness of sustainability in the construction industry, it is of great importance to recycle waste materials for producing high-performance concrete (HPC). This aligns with the twelfth Sustainable Development Goal (SDG) of the United Nations, emphasizing responsible production and consumption, especially concerning the production of HPC using waste materials and energy-efficient methods. The review evaluates the purposeful utilization of recycled waste materials to improve the engineering characteristics of HPC, taking into consideration pertinent literature. It encompasses a comparative evaluation of strength development, water absorption, microstructures, and x-ray diffraction (XRD) analyses of HPC manufactured with different types of recycled waste materials. The key result of the review showed that using incinerated bottom ash (IBA) below 25% and incorporating 40% copper slag can enhance HPC’s mechanical performance. Additionally, recycled coarse aggregate (RCA) can replace up to 50% of conventional aggregate in self-compacting HPC with minimal impact on durability properties. In HPC cement substitution research, fly ash, silica fume, and metakaolin are prominent due to their availability, with fly ash showing remarkable durability when used as a 15% cement replacement. This thorough review offers valuable insights for optimizing the utilization of recycled waste materials in the development of environmentally friendly HPC. Doi: 10.28991/CEJ-2023-09-11-020 Full Text: PDF